Sie sind auf Seite 1von 4

# 1

Formula

Eulers method

## Taylor series expansion

f ( xi ) 2 f 3 (xi ) 3 f ( n ) ( xi ) n
f ( xi +1 ) = f (xi ) + f ( xi )h + h + h + ... + h + Rn
2! 3! n!
h = xi +1 xi

## Forward difference Approximation of the First Derivative

f (xi +1 ) f ( xi )
f (xi ) =
h
Backward difference Approximation of the First Derivative

f (xi ) f ( xi 1 )
f (xi ) =
h
Centered difference Approximation of the First Derivative

f (xi +1 ) f ( xi 1 )
f (xi ) =
2h
False Position method

f ( xu )(xl xu )
xr = xu
f ( xl ) f ( xu )
Newton-Raphson formula

f ( xi )
xi +1 = xi
f (xi )
Secant method

f ( xi )(xi 1 xi )
xi +1 = xi
f (xi 1 ) f (xi )
Modified secant method

xi f (xi )
xi +1 = xi
f (xi + xi ) f (xi )
2

t = 100%
true value

## present approximation - previous approximation

a = 100%
present approximation
Relaxation

## Least-Squares Fit of a Straight Line

n xi a 0 y i
x x 2 a = x y
i i 1 i i
n xi yi xi yi
a1 =
n xi2 ( xi )
2

a0 = y a1 x
n ( xi yi ) ( xi )( yi )
r = r2 =
n xi2 ( xi ) n yi2 ( yi )
2 2

## General Form of Newtons Interpolating Polynomial

f n 1 ( x ) = b1 + b2 ( x x1 ) + ... + bn ( x x1 )( x x2 )L ( x xn 1 )

b1 = f (x1 )
b2 = f [x2 , x1 ]
b3 = f [x3 , x2 , x1 ]
M
bn = f [xn , xn 1 ,..., x2 , x1 ]

Lagrange polynomials
n
f n 1 (x ) = Li ( x ) f (xi )
i =1

n x xj
Li ( x ) =
j =1 xi x j
j i
3

## The trapezoidal rule

f (a ) + f (b )
I = (b a )
2

h n 1
ba
I= f ( x0 ) + 2 f ( xi ) + f ( xn ) h=
n
2 i =1

## Simpsons 1/3 Rule

h
I= [ f (x0 ) + 4 f (x1 ) + f (x2 )]
3
n 1 n 2
f ( x0 ) + 4 f (x ) + 2 f (x ) + f (x )
i j n

I = (b a )
i =1,3, 5 j =2, 4,6

3n

## Simpsons 3/8 Rule

f ( x0 ) + 3 f ( x1 ) + 3 f ( x2 ) + f ( x3 )
I = (b a )
8

Eulers Method

yi +1 = yi + f (ti , yi ) h

Heuns Method

yi +1 = yi +
(
f (ti , yi ) + f ti +1 , yi0+1
h
)
2

## Classical Fourth-Order Runge-Kutta Method

1
yi +1 = yi + (k1 + 2k2 + 2k3 + k 4 )h
6

k1 = f (ti , yi )
1 1
k 2 = f ti + h, yi + k1h
2 2
1 1
k 3 = f t i + h, y i + k 2 h
2 2
k 4 = f (ti + h, yi + k3h )
4

## Centered Finite Difference Formula

f ( xi 1 ) + f ( xi +1 )
f (xi ) =
2h
f ( xi 1 ) 2 f (xi ) + f ( xi +1 )
f ( xi ) =
h2
h = xi +1 xi = xi xi 1

f ( xi 1 ) = f ( xi +1 ) 2hf ( xi )
f (xi +1 ) = f ( xi 1 ) + 2hf ( xi )

udv = uv vdu
e du = e
u u

sin u du = cos u
cos u du = sin u